To Make or Not to Make Hypotheses? Lesage, Cramer, and Newtonian Heritage in 18th Century Geneva - Miqueu, Adrien (Foundations of Science, 2026)
This article examines the complexities of Newton’s legacy in the 18th century. Physicists were divided between a mathematical approach coupled with agnosticism about the nature of phenomena, on the one hand, and a speculative programme of research into causality, on the other hand. Geneva provides an illustrative example of these confrontations, as supporters of both currents coexisted within the small scholarly milieu centred around the Académie des Pasteurs. We will show that each of these approaches is identified with a scientific thought style rooted in a specific interpretation of Calvinism and a certain political orientation. In particular, the cases of George-Louis Lesage, Gabriel Cramer and Jean-Louis Calandrini, whose interpretations of the theory of universal gravitation greatly varied, reflect the general evolution of what constitutes an explanation in physics.